High prevalence of diabetes in patients with rheumatoid arthritis: results from a questionnaire survey linked to claims data. (7th November 2017) - Albrecht, Katinka; Luque Ramos, Andres; Hoffmann, Falk; Redeker, Imke; Zink, Angela
Abstract: Objectives: To investigate the prevalence of diabetes in patients with RA and the impact of diabetes on self-reported outcomes and health care. Methods: RA patients between the ages of 18 and 79 years were randomly selected from a nationwide statutory health insurance fund and were surveyed about rheumatological care and disease burden. Comorbid diabetes (E10–14) was analysed regarding age, sex, BMI and socioeconomic status. Disease burden, comorbidity and prescriptions were compared in RA patients with and without diabetes. Predictors of rheumatological care were identified by multivariate regression. Results: Of the 2535 RA patients, 498 (20%) had diabetes. Diabetes was more frequent in males, in older patients, in patients with a higher BMI and in those with a lower socioeconomic status. All disease outcomes were poorer in RA–diabetes patients and were mainly attributable to a higher BMI. RA–diabetes patients received less DMARDs (40% vs 48%) and had more hospital stays (41% vs 30%) than patients without diabetes (all P < 0.05). Rates of cardiovascular disease (35% vs 15%), depression (39% vs 26%) and renal failure (23% vs 8%) were higher in RA–diabetes patients (all P < 0.0001). They were less frequently treated by rheumatology specialists: 57% vs 67%; odds ratio = 0.64 (95% CI: 0.45, 0.92), after controlling for confounders. Conclusion: The prevalence of diabetes in patients with RA is high and is associated with known sociodemographic factors. More than 40% of patients with RA and diabetes were not under rheumatological care even though they reported a high disease burden, were frequently hospitalized and often presented with further comorbidities.